Submerged Groundwater Discharges as Source of Fecal Material in Protected Karstic Coastal Areas. (5th March 2018) - Kantun Manzano, Cristian; Arcega-Cabrera, Flor; Derrien, Morgane; Noreña-Barroso, Elsa; Herrera-Silveira, Jorge
Abstract : Coastal zones are vital for their ecosystem services and socioeconomic value. Accordingly, several zones have been protected to limit anthropogenic development and to avoid environmental degradation. Nevertheless, some of these protected areas keep deteriorating probably related with anthropogenic contributions not considered in legislation. Specifically, submerged groundwater discharges (springs) could be releasing anthropogenic materials carried from remote inland areas to the coast. Here we evaluate the role and temporal variation of submerged groundwater discharges as sources of anthropogenic materials using the 5β -stanol C27 markers in the natural protected area of Dzilam de Bravo, Yucatán, Mexico. Results demonstrate that (1) submerged groundwater discharge flux velocity and direction vary between hydrological season, exhibiting higher flow rates in Nortes season contrary to dry season and (2) the presence of coprostanol and epicoprostanol (anthropogenic fecal matter markers) in sediments surrounding the submerged groundwater discharges provides proof of allochthonous anthropogenic fecal material in a protected area, probably from remote inland sites. Thus, it is vitally important that inland anthropogenic materials transported in groundwater and released in the coastal environment by submerged groundwater discharges be considered in protection plans, like protection perimeters, for coastal zones.